DEVELOPING SPEAKING SKILLS BY PERFORMANCE OF A SHORT DRAMA - Wahdini, Lili (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2013)
Â This article is aimed at presenting an alternative to anticipate the problems faced by students in speaking activities. One of the techniques that can be used to increase studentsâ€™ ability in speaking is by performing a short drama in English class. Drama provides more chance for the students to speak and in English fluently and accurately as the students do not feel stress in learning. Moreover, the students are motivated to speak and express their feeling. Therefore, by performing a short drama, it can create a warm and happy atmosphere in the classroom.Â